Minorities, Human Capital and Long-Run Development: Persistence of Armenian and Greek Influence in Turkey - Cemal Eren Arbatli; Gunes Gokmen (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study the long-term economic legacy of highly-skilled minorities a century after their wholesale expulsion. Using mass expulsions of Armenian and Greek communities of the Ottoman Empire in the early 20th century as a unique natural experiment of history, we show that districts with greater presence of Armenian and Greek minorities at the end of the 19th century are systematically more densely populated, more urbanized, and more developed today. Results are robust to accounting for an extensive set of geographical and historical factors of development and minority settlement patterns. Matching type estimators, instrumental variable regressions, and a sub-province level case study corroborate our findings. Importantly, we provide evidence on the channels of persistence. Armenian and Greek contribution to long-run development is largely mediated by their legacy on local human capital accumulation. In comparison, the mediating effect of minority asset transfer on development appears less important.
Keywords: O10; O43; P48; N40; Z12; 330; human capital; economic development; expulsion; minorities; ethnicity; Armenians; Greeks; persistence